Variations between pharmacist- and doctor-obtained medication histories and their potential significance. Issue 2 (12th March 2012) - Gaffney, G.
Abstract : Background: NICE recommends that pharmacists be involved in obtaining medication histories. 1 Previous studies have shown variations between the medication histories obtained by pharmacists and doctors. 2 3 Purpose: This study aimed to compare the medication histories obtained by both professionals, assess the extent of any variations found and grade their potential clinical significance. Materials and methods: Unintentional variations between pharmacist- and doctor-obtained medication histories were independently assessed by a consultant and clinical pharmacist for their potential to cause patient harm, using the National Co-ordinating Council for Medication Error Reporting and Prevention index. The relationship between variables was investigated using Mann–Whitney U and Kruskal–Wallis Tests. Results: Unintentional variations were identified in the medication histories of 63% of patients. Variations included: drug omission (72%), different dose (17%), different frequency (7%), drug commission (3%) and dose omission (0.7%). 13 patients had >4 unintentional variations. The mean number of medicines being taken was 7, while the mean number of unintentional variations was 3.4. A significant positive correlation was found between the number of medications being taken and the number of unintentional variations. No significant difference in the number of variations per patient across either the different grades or specialties of doctors was found. Up to 13% of variations had the potential to cause patient harm. Conclusions: The study confirms the results of other research which showed that a pharmacist takes more complete medication histories compared to doctors. A more multidisciplinary approach should be taken when admitting patients; this should involve a pharmacist to obtain medication histories. The emergency department is the ideal setting to undertake this process as the maximum impact of involving a pharmacist could be delivered at this early stage of the patient journey.